A metal carbide electrocatalyst derived from Fe-doped MOF and its preparation method and application

By doping Fe in MOF-derived materials, metal carbide electrocatalysts with rich pores and high specific surface area were prepared, which solved the problem of slow kinetics of the oxygen reduction reaction of zinc-air batteries and achieved low-cost and efficient catalytic performance.

CN115395027BActive Publication Date: 2025-04-01ANHUI UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211052432.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-31
Publication Date
2025-04-01
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

The kinetics of existing zinc-air batteries are slower, resulting in limited practical applications. Most of the high-efficiency catalysts are precious metals, with high costs and difficult to meet the low-cost and efficient catalyst needs.

Method used

By doping Fe into MOF-derived materials, a metal carbide electrocatalyst was prepared, and hydrothermal reaction and high temperature calcination were used to form an olive-shaped material with rich pores and high specific surface area, and Fe-Nx and Fe3C dual active sites were added.

Benefits of technology

The catalytic kinetics and mass transfer rate are improved, the stability of the oxygen reduction reaction and the anti-methanol toxicity are enhanced, and the catalytic performance is improved at low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115395027B_ABST
    Figure CN115395027B_ABST
Patent Text Reader

Abstract

The invention discloses a metal carbide electrocatalyst derived from Fe-doped MOF, and a preparation method and application thereof. The preparation method comprises the following steps: dissolving H2L-N in a DMF solution to form a ligand solution; uniformly mixing a zinc salt, an iron salt and water to obtain a metal ion solution; uniformly mixing the metal ion solution and the ligand solution at room temperature to obtain a reaction solution; subjecting the reaction solution to a hydrothermal reaction; centrifuging, washing, drying and then calcining the suspension obtained after the hydrothermal reaction to obtain the metal carbide electrocatalyst derived from Fe-doped MOF; the structural formula of H2L-N is as follows: #imgabs0# The preparation method of the invention has simple procedures, is easy to reproduce, and is convenient for industrial production. The obtained material can be used as an oxygen reduction catalyst in disposable zinc-air batteries, and has excellent electrochemical properties under alkaline conditions (0.1M KOH).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a metal carbide electrocatalyst derived from Fe-doped MOF, and a preparation method and application thereof. Background Art

[0002] At present, the country attaches great importance to the prevention and protection of the ecological environment, so the demand for developing more clean, efficient and sustainable energy conversion and storage devices is also increasing. Zinc-air batteries (ZAB) mainly involve oxygen reduction reaction (ORR), and its slow kinetics greatly limits the practical application of zinc-air batteries. In order to increase the speed and efficiency of the reaction, high-performance electrocatalytic materials are usually required to increase its half-wave potential (E 1 / 2 ), but the current efficient catalysts are still precious metals. Therefore, finding efficient and stable low-cost catalysts to solve the defects of zinc-air batteries is the future development trend.

[0003] In recent years, a new frontier in the field of catalysis and materials science is single-atom catalysts (SACs), whose active centers are dispersed on functional carriers, which have become one of the hottest research topics. For example, Chinese patent application document with publication number CN110961134A discloses a method for synthesizing single-atom catalysts, which can synthesize a variety of metal single-atom catalysts. It is a general method and can be used for large-scale synthesis of single-atom catalysts, which solves the shortcomings of other existing technologies that are complex to synthesize and difficult to prepare on a large scale; for example, Chinese patent application document with publication number CN113871639A discloses a copper single atom / atom cluster catalyst. In the prepared catalyst material, Cu is loaded on the carbon material in the form of coexistence of copper single atoms and atom clusters, and its ORR catalytic activity is very excellent. Its half-wave potential and Tafel slope are much better than those of pure nitrogen-doped porous carbon materials and commercial platinum carbon, and it has better resistance to methanol poisoning, and can be used in fuel cells or metal-air batteries; however, the above catalyst has the problem of few active sites, which affects the catalytic performance of the catalyst. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a new type of electrocatalyst with multiple active sites and good catalytic performance.

[0005] The present invention solves the above technical problems through the following technical means:

[0006] A method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF comprises the following steps:

[0007] S1. Dissolve H2L-N in DMF solution to form a ligand solution; mix zinc salt, iron salt and water to obtain a metal ion solution;

[0008] S2, uniformly mixing the metal ion solution and the ligand solution at room temperature to obtain a reaction solution;

[0009] S3, subjecting the reaction solution in S2 to a hydrothermal reaction;

[0010] S4, centrifuging, washing, drying and then calcining the suspension obtained after the hydrothermal reaction in S3 to obtain the metal carbide electrocatalyst derived from Fe-doped MOF;

[0011] Wherein, the structural formula of the H2L-N is as follows:

[0012]

[0013] Beneficial effects: The composite material prepared by the present invention is an olive-shaped material with abundant pores, high specific surface area and a large amount of Fe-N x The dual active sites of Fe3C can improve the catalytic kinetics and mass transfer rate. Secondly, the Fe nanoparticles in the Fe3C nanoparticles are coated with a carbon layer to form a core-shell structure, which enhances the stability of the composite material prepared by the present invention during the ORR process.

[0014] Preferably, in S1, the mass-to-volume ratio of the H2L-N and DMF solution is 1 mg: 0.3-0.6 mL; the volume ratio of the total mass of the zinc salt and the iron salt to H2O is 1 mg: 0.5-0.9 mL.

[0015] Preferably, in S1, the mass ratio of the total mass of the zinc salt and the iron salt to the mass of H2L-N is 1-1.5:1.

[0016] Preferably, in S1, the zinc salt is Zn(NO3)2·6H2O; and the iron salt is Fe(NO3)3·9H2O.

[0017] Preferably, in S3, the temperature of the hydrothermal reaction is 70-90°C and the time is 20-35h.

[0018] Preferably, in S4, the centrifugal conditions are: rotation speed 8000-10000 r / min, time 3-5 min; the drying conditions are: temperature 45-55° C., time 8-12 h.

[0019] Preferably, in S4, the calcination includes two calcinations; the process of the two calcinations includes: loading the dried material into a porcelain boat, placing it in a tubular furnace for a first heating calcination; acid leaching in a 0.3-0.6M H2SO4 solution for 20-30h and then loading it into a porcelain boat, placing it in a tubular furnace for a second heating calcination under the same conditions as the first heating calcination.

[0020] Preferably, in S4, the calcination temperature is 920-950°C, the time is 1.5-2.5h, and the heating rate is 3-5°C / min.

[0021] The present invention also provides a metal carbide electrocatalyst derived from Fe-doped MOF, which is prepared by using the preparation method of the metal carbide electrocatalyst derived from Fe-doped MOF.

[0022] The present invention also proposes an application of the metal carbide electrocatalyst derived from Fe-doped MOF as an oxygen reduction catalyst in a disposable zinc-air battery.

[0023] The advantages of the present invention are:

[0024] (1) The present invention uses H2L-N as a ligand and zinc salt and iron salt as metal salts to prepare an olive-shaped material with no surface collapse, good overall morphology, and excellent thermal stability;

[0025] (2) The olive-shaped material prepared by the present invention has the advantages of small product particle size and multiple active sites, and can be used as an oxygen reduction catalyst in disposable zinc-air batteries, and has excellent electrochemical performance under alkaline conditions (0.1 M KOH);

[0026] (3) The preparation process adopted by the present invention is simple, easy to reproduce, has high yield, and is convenient for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a process flow chart of Example 2 of the present invention;

[0028] Figure 2 (a) is a scanning electron microscope (SEM) image of the metal-organic framework material (MOF) prepared from zinc salt in Comparative Example 2, (b) is a scanning electron microscope (SEM) image of the Zn5Fe1-MOF prepared in Example 2, and (c) is a scanning electron microscope (SEM) image of the composite material Fe3C-FeN / NC-5 after two high-temperature carbonizations of the Zn5Fe1-MOF prepared in Example 2;

[0029] Figure 3 Transmission electron microscopy (TEM) (ab) and high-resolution transmission electron microscopy (HRTEM) (c) images of the composite material prepared in Example 2 of the present invention (the insets in Figures b and c are the particle size distribution and regional electron diffraction of Fe3C nanoparticles, respectively);

[0030] Figure 4Polarization curve (a) of the oxygen reduction reaction of the composite material Fe3C-FeN / NC-5 prepared in Example 2 of the present invention in an O2-saturated 0.1M KOH aqueous solution at 1600 rpm, the corresponding Tafel slope (b), the stability test curve (c), the methanol tolerance curve (d), and the polarization curve after adding 1M KSCN solution (e);

[0031] Figure 5 (a) Polarization curve and power density curve of the zinc-air battery prepared from the composite material Fe3C-FeN / NC-5 prepared in Example 2 of the present invention, (b) at 10 mA / cm 2 Specific capacity curve under the conditions, (c) at 10mA / cm 2 Discharge curve under different conditions, (d) discharge curve under different current densities, (e) open circuit voltage of zinc-air battery, and (f) LED light powered by zinc-air battery. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0034] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0035] In the examples of the present invention, zinc nitrate hexahydrate and ferric nitrate nonahydrate were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; zinc acetate was purchased from Xilong Chemical Plant in Shantou City, Guangdong Province; potassium hydroxide, anhydrous ethanol, and Nafion solution were purchased from Sinopharm Chemical Reagent Co., Ltd.; N,N-dimethylformamide (DMF) was purchased from Jiangsu Qiangsheng Functional Chemical Co., Ltd.; all of the above raw materials were analytically pure.

[0036] H2L-N is self-made and its structural formula is as follows:

[0037]

[0038] The preparation process is as follows: 2,6-diacetylpyridine (4.90 g, 30 mmol), N,N-dimethylformamide dimethyl acetal (DMF-DMA) (20 mL), and xylene (30 mL) were added to a 100 mL three-necked round-bottom flask. The reaction was heated at 140 ° C for 24 hours. After cooling to room temperature, 6.52 g of light yellow solid was collected by filtration, washed with saturated NaCl, and dried at 80 ° C. The solid was used in the next step without any purification. The product dried at 80 ° C was directly added to a 100 mL three-necked round-bottom flask, and then CH3COONH4 (5.5 g, 7.1 mmol), CH3COOH (24 mL), and ethyl acetoacetate (22 mL) were added. The mixture was stirred at 100 ° C. After 12 hours, the excess CH3COOH was removed by rotary evaporator, and CH3COONH4 was removed by water washing. The residual yellow solid was stored in the flask without further purification. The yellow solid product stored in the flask was added to a 100 mL three-necked round-bottom flask, followed by H2O36 mL), EtOH (10 mL) and NaOH (10 g, 0.25 mol). The mixture was stirred at 70 ° C. After 8 hours, dilute HCl was added to the remaining aqueous solution until the pH of the solution was 3, and 5.6 g of white solid was collected by filtration. Then 1,3-(bis(6-(2-methyl)nicotinyl))pyridine (H2L-N) was obtained after drying under vacuum (three-step yield was 53%).

[0039] Among the test devices used in the present invention, the scanning electron microscope (SEM, FlexSEM1000) was purchased from Hitachi High-Tech Corporation; the transmission electron microscope (TEM, JEM2100F) was purchased from JEOL Corporation of Japan; and the electrochemical workstation was purchased from Shanghai Chenhua Instrument Co., Ltd.

[0040] Example 1

[0041] The preparation method of the metal carbide electrocatalyst based on Fe-doped MOF derived from the present invention comprises the following steps:

[0042] S1: Weigh 50 mg of H2L-N and place it in a beaker, dissolve it in 15 mL of DMF solution to form a ligand solution; weigh 50 mg of Zn(NO3)2·6H2O and 5 mg of Fe(NO3)3·9H2O and add them to 45 mL of deionized water and stir evenly to obtain a metal ion solution;

[0043] S2: Add the metal ion solution in S1 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution;

[0044] S3: placing the reaction solution in S2 in a high pressure reactor for hydrothermal reaction at 80°C for 24h;

[0045] S4: The suspension after hydrothermal treatment is centrifuged, washed and dried. The centrifugal conditions are: speed 8000r / min, time 3min, and the drying conditions are: temperature 50℃, time 12h; 50mg of the dried material is loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 5℃ / min, and heated for 2h. Acid leaching in 0.5M H2SO4 solution for 24h, then loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 5℃ / min, and heated for 2h to obtain an olive-shaped composite material, i.e., the metal carbide electrocatalyst derived from Fe-doped MOF.

[0046] Example 2

[0047] Figure 1 The process flow chart of the preparation method of the metal carbide electrocatalyst derived from Fe-doped MOF proposed in the present invention is shown in FIG. Figure 1 , the preparation method comprises the following steps:

[0048] S1: Weigh 50 mg of H2L-N into a beaker and dissolve it in 15 mL of DMF solution to form a ligand solution; weigh 46 mg of Zn(NO3)2·6H2O and 9 mg of Fe(NO3)3·9H2O and add them into 45 mL of deionized water and stir evenly to obtain a metal ion solution;

[0049] S2: Add the metal ion solution in S1 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution;

[0050] S3: placing the reaction solution in S2 in a high pressure reactor for hydrothermal reaction at 80°C for 24h;

[0051] S4: The suspension after hydrothermal treatment was centrifuged, washed and dried. The centrifugal conditions were: speed 8000r / min, time 3min, and the drying conditions were: temperature 50℃, time 12h; 50mg of the dried material Zn5Fe1-MOF was loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 5℃ / min, and heated for 2h. After acid leaching in 0.5M H2SO4 solution for 24h, it was loaded into a porcelain boat again, placed in a tube furnace, heated to 920℃ at a heating rate of 5℃ / min, and heated for 2h to obtain an olive-shaped composite material, namely, Fe3C-FeN / NC-5, a metal carbide electrocatalyst derived from Fe-doped MOF.

[0052] Example 3

[0053] The present invention provides a method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF, the method comprising the following steps:

[0054] S1: Weigh 50 mg of H2L-N into a beaker and dissolve it in 15 mL of DMF solution to form a ligand solution; weigh 27.5 mg of Zn(NO3)2·6H2O and 27.5 mg of Fe(NO3)3·9H2O and add them into 45 mL of deionized water and stir evenly to obtain a metal ion solution;

[0055] S2: Add the metal ion solution in S1 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution;

[0056] S3: placing the reaction solution in S2 in a high pressure reactor for hydrothermal reaction at 80°C for 24h;

[0057] S4: The suspension after hydrothermal treatment is centrifuged, washed and dried. The centrifugal conditions are: speed 8000r / min, time 3min, and the drying conditions are: temperature 50℃, time 12h; 50mg of the dried material is loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 5℃ / min, and heated for 2h. After acid leaching in 0.5M H2SO4 solution for 24h, it is loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 5℃ / min, and heated for 2h to obtain an olive-shaped composite material, i.e., the metal carbide electrocatalyst derived from Fe-doped MOF.

[0058] Example 4

[0059] The preparation method of the metal carbide electrocatalyst based on Fe-doped MOF derived from the present invention comprises the following steps:

[0060] S1: Weigh 50 mg of H2L-N into a beaker and dissolve it in 15 mL of DMF solution to form a ligand solution; weigh 9 mg of Zn(NO3)2·6H2O and 46 mg of Fe(NO3)3·9H2O and add them into 45 mL of deionized water and stir evenly to obtain a metal ion solution;

[0061] S2: Add the metal ion solution in S1 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution;

[0062] S3: placing the reaction solution in S2 in a high pressure reactor for hydrothermal reaction at 80°C for 24h;

[0063] S4: The suspension after hydrothermal treatment is centrifuged, washed and dried. The centrifugal conditions are: speed 8000r / min, time 3min, and the drying conditions are: temperature 50℃, time 12h; 50mg of the dried material is loaded into a porcelain boat, placed in a tube furnace and heated to 920℃ at a heating rate of 5℃ / min for 2h. Acid leaching in 0.5M H2SO4 solution for 24h, then loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 5℃ / min for 2h to obtain an olive-shaped composite material, i.e., the metal carbide electrocatalyst derived from Fe-doped MOF.

[0064] Example 5

[0065] The preparation method of the metal carbide electrocatalyst based on Fe-doped MOF derived from the present invention comprises the following steps:

[0066] S1: Weigh 50 mg of H2L-N into a beaker and dissolve it in 20 mL of DMF solution to form a ligand solution; weigh 9 mg of Zn(NO3)2·6H2O and 41 mg of Fe(NO3)3·9H2O and add them into 40 mL of deionized water and stir evenly to obtain a metal ion solution;

[0067] S2: Add the metal ion solution in S1 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution;

[0068] S3: placing the reaction solution in S2 in a high pressure reactor for hydrothermal reaction at 80°C for 24h;

[0069] S4: The suspension after hydrothermal treatment is centrifuged, washed and dried. The centrifugal conditions are: speed 8000r / min, time 3min, and the drying conditions are: temperature 50℃, time 12h; 50mg of the dried material is loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 5℃ / min, and heated for 2h. After acid leaching in 0.5M H2SO4 solution for 24h, it is loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 5℃ / min, and heated for 2h to obtain an olive-shaped composite material, i.e., the metal carbide electrocatalyst derived from Fe-doped MOF.

[0070] Example 6

[0071] The preparation method of the metal carbide electrocatalyst based on Fe-doped MOF derived from the present invention comprises the following steps:

[0072] S1: Weigh 50 mg of H2L-N into a beaker and dissolve it in 25 mL of DMF solution to form a ligand solution; weigh 20 mg of Zn(NO3)2·6H2O and 35 mg of Fe(NO3)3·9H2O and add them into 35 mL of deionized water and stir evenly to obtain a metal ion solution;

[0073] S2: Add the metal ion solution in S1 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution;

[0074] S3: placing the reaction solution in S2 in a high pressure reactor for hydrothermal reaction at 70°C for 35h;

[0075] S4: The suspension after hydrothermal treatment is centrifuged, washed and dried. The centrifugal conditions are: speed 9000r / min, time 5min, and the drying conditions are: temperature 45℃, time 10h; 50mg of the dried material is loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 3℃ / min, and heated for 2.5h. Acid leaching in 0.3M H2SO4 solution for 20h, then loaded into a porcelain boat, placed in a tube furnace, heated to 920℃ at a heating rate of 3℃ / min, and heated for 2.5h to obtain an olive-shaped composite material, i.e., the metal carbide electrocatalyst derived from Fe-doped MOF.

[0076] Example 7

[0077] The preparation method of the metal carbide electrocatalyst based on Fe-doped MOF derived from the present invention comprises the following steps:

[0078] S1: Weigh 50 mg of H2L-N into a beaker and dissolve it in 30 mL of DMF solution to form a ligand solution; weigh 9 mg of Zn(NO3)2·6H2O and 46 mg of Fe(NO3)3·9H2O and add them into 49.5 mL of deionized water and stir evenly to obtain a metal ion solution;

[0079] S2: Add the metal ion solution in S1 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution;

[0080] S3: placing the reaction solution in S2 in a high pressure reactor for hydrothermal reaction at 90°C for 20h;

[0081] S4: The suspension after hydrothermal treatment is centrifuged, washed and dried. The centrifugal conditions are: speed 10000r / min, time 4min, and the drying conditions are: temperature 55℃, time 8h; 50mg of the dried material is loaded into a porcelain boat, placed in a tube furnace, heated to 950℃ at a heating rate of 4℃ / min, and heated for 1.5h. Acid leaching in 0.6M H2SO4 solution for 30h, then loaded into a porcelain boat, placed in a tube furnace, heated to 950℃ at a heating rate of 4℃ / min, and heated for 1.5h to obtain an olive-shaped composite material, i.e., the metal carbide electrocatalyst derived from Fe-doped MOF.

[0082] Example 8

[0083] The preparation method of the metal carbide electrocatalyst based on Fe-doped MOF derived from the present invention comprises the following steps:

[0084] S1: Weigh 50 mg of H2L-N into a beaker and dissolve it in 30 mL of DMF solution to form a ligand solution; weigh 30 mg of Zn(NO3)2·6H2O and 45 mg of Fe(NO3)3·9H2O and add them into 37.5 mL of deionized water and stir evenly to obtain a metal ion solution;

[0085] S2: Add the metal ion solution in S1 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution;

[0086] S3: placing the reaction solution in S2 in a high pressure reactor for hydrothermal reaction at 85°C for 30h;

[0087] S4: The suspension after hydrothermal treatment is centrifuged, washed and dried. The centrifugal conditions are: speed 9000r / min, time 4min, and the drying conditions are: temperature 55℃, time 8h; 50mg of the dried material is loaded into a porcelain boat, placed in a tube furnace, heated to 935℃ at a heating rate of 4℃ / min, and heated for 1.5h. Acid leaching in 0.6M H2SO4 solution for 30h, then loaded into a porcelain boat, placed in a tube furnace, heated to 935℃ at a heating rate of 4℃ / min, and heated for 1.5h to obtain an olive-shaped composite material, i.e., the metal carbide electrocatalyst derived from Fe-doped MOF.

[0088] Comparative Example 1

[0089] S1: Weigh 50 mg of H2L-N into a beaker and dissolve it in 30 mL of DMF solution to form a ligand solution;

[0090] S2: Weigh 55 mg of Zn(C2H3O2)2 and add it into 49.5 mL of deionized water and stir evenly to obtain a metal ion solution;

[0091] S3: Add the metal ion solution in S2 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution with flocculent substances produced;

[0092] S4: The reaction liquid in S3 is placed in a high pressure reactor and hydroheated at 90°C for 20 hours. The suspension after hydroheating is centrifuged, washed and dried. The centrifugation conditions are: speed 10000r / min, time 4min, and the drying conditions are: temperature 55°C, time 8h;

[0093] S5: 50 mg of the dried material in S4 was placed in a porcelain boat, and heated to 950°C in a tube furnace at a heating rate of 4°C / min for 1.5 h. After acid leaching in 0.6M H2SO4 solution for 30 h, the material was placed in a porcelain boat again, and placed in a tube furnace at a heating rate of 4°C / min for 1.5 h to obtain a morphology-free composite material.

[0094] Comparative Example 2

[0095] S1: Weigh 50 mg of H2L-N and place it in a beaker, dissolve it in 15 mL of DMF solution to form a ligand solution; weigh 55 mg of Zn(NO3)2·6H2O and add it to 45 mL of deionized water and stir evenly to obtain a metal ion solution;

[0096] S2: Add the metal ion solution in S1 to the ligand solution in S1 at room temperature, and stir ultrasonically for 30 minutes to mix the materials evenly to obtain a reaction solution;

[0097] S3: placing the reaction solution in S2 in a high pressure reactor for hydrothermal reaction at 80°C for 24h;

[0098] S4: The hydrothermal suspension is centrifuged, washed, and dried to obtain a metal-organic framework material (MOF) prepared by zinc salt; the centrifugal conditions are: speed 8000r / min, time 3min, and the drying conditions are: temperature 50°C, time 12h.

[0099] Depend on Figure 2 It can be seen that when zinc metal is used as the metal source, the MOF sample is olive-shaped and has a small size ( Figure 2 a), when metallic iron is added, the MOF sample presents a similar olive shape ( Figure 2 b). In addition, after high-temperature calcination, it can be found that the catalyst maintains an intact olive-shaped morphology without being damaged ( Figure 2 c). The MOF sample that was not damaged after high-temperature calcination showed that the sample had good thermal stability.

[0100] For the Zn5Fe1-MOF derived composite Fe3C-FeN / NC-5, the morphology and composition of the product of Example 2 were further discussed using TEM. Figure 3 Transmission electron microscopy (ab) and high-resolution transmission electron microscopy (c) images of the composite material prepared in Example 2 of the present invention (the insets in Figure b and Figure c are the particle size distribution and regional electron diffraction of Fe3C nanoparticles, respectively); from the TEM image, it was observed that the Fe3C-FeN / NC-5 contained obvious granular material ( Figure 3 ,a,b),In addition, Figure 3 The inset of b roughly shows the size distribution of Fe3C nanoparticles (NPs), with most particles in the range of 10–12 nm. x Fe y The structural aspects of the -MOF can explain why the final Fe3C nanoparticles have a small particle size: Fe(III) is a chelated environment surrounded by N / O atoms, which is suitable for isolating the Fe source, and the Zn source acts as a pore former, which can also effectively avoid their diffusion / aggregation during the thermal treatment. Figure 3 c. The HRTEM image shows that the spacing between the lattice fringes is 0.201 nm, corresponding to the (103) crystal plane, indicating the presence of Fe3C nanocrystals. In addition, the presence of (103), (113), (312) and (140) diffraction rings in the selected area electron diffraction (SAED) pattern further proves the existence of Fe3C ( Figure 3 c). It can be clearly seen that Fe3C NPs are coated by a carbon layer with a thickness of about 5 nm. The formation of this core-shell structure is crucial for maintaining stable electrocatalytic performance for a long time under harsh conditions. In addition, this porous structure can expose more active sites and promote the penetration of H2O, effectively increasing the contact opportunity between water and electrocatalysts.

[0101] In addition, the electrochemical properties of the samples were characterized on a CHI760D electrochemical workstation in a three-electrode system. 1 mg of the catalyst prepared in Example 2 was dispersed in a solution containing ethanol / H2O (1 / 1, v / v) (192 μL) and Nafion (5wt%, 8 μL) and ultrasonically treated for 30 minutes. 10 μL of the sample suspension was drop-cast onto a glassy carbon electrode (4 mm in diameter) and then dried under ambient conditions to make a working electrode. The mass loading of the active material on the working electrode was controlled to be approximately 0.5 mg / cm 2 A graphite electrode was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode to complete the three-electrode system. For the measurement, a 0.1 M KOH (pH = 13) aqueous solution was used as the electrolyte. Using the formula E RHE =E SCE+0.098+0.0591pH, converting the potentials reported in this study to values ​​referenced to the reversible hydrogen electrode (RHE), where E SCE The potential is applied to the saturated calomel electrode reference electrode. Before the electrochemical measurements, the potential cycle is repeated in the potential window from -1 to 0 V until a reproducible CV curve is obtained before the measurement (scan rate is 10 mV / s). The polarization curve of ORR is recorded with a linear potential scan at a scan rate of 10 mV / s. Long-term stability testing and anti-methanol toxicity testing are performed using chronoamperometry.

[0102] The ORR performance of the product is as follows: Figure 4 As shown in a, its half-wave potential E 1 / 2 =0.932V, limiting current J L =5.65mA / cm 2 ; Tafel slope is 78mV / dec( Figure 4 b). In addition, the ORR stability of the catalyst was tested at a voltage of 0.8 V. Figure 4 c, after 24 h of continuous reaction, the ORR current retention rate was 91.2%, demonstrating the excellent ORR stability of the catalyst. Long-term durability is an important criterion for evaluating catalyst performance. Figure 4 d It can be seen that after the introduction of 1 mL of methanol at 200 s, the performance of Fe3C-FeN / NC-5 hardly changed, indicating that Fe3C-FeN / NC-5 has strong resistance to methanol poisoning. Figure 4 e The Fe-N was poisoned by adding 1 mL of 1 mol / L KSCN solution to 0.1 mol / L KOH electrolyte solution saturated with O2. x At 1600 rpm, the LSV curve (shown in the figure for 1M KSCN) differed by 105 mV from the initial LSV curve (shown in the figure for Initial), which verified that one of its active sites was Fe-N x .

[0103] In addition, the performance and stability of the disposable zinc-air battery (ZAB) of the catalyst prepared in Example 2 were further tested. Figure 5 As shown in a, the catalyst 2 The peak power density is 283mW / cm 2 , exceeding the peak power density (300 mA / cm2) of commercially available Pt / C (20 wt%) catalysts in the same Zn-air battery configuration. 2 164mW / cm 2 ). Then at 10mA / cm 2The specific capacity of the assembled primary battery was measured. If normalized to the consumed mass of zinc, the specific capacity of Fe3C-FeN / NC-5 is 835 mAh / g Zn , which is higher than the 652mAh / g of commercially available Pt / C (20wt%) Zn ( Figure 5 b). At 10 mA / cm 2 When the Zn-air battery assembled by Fe3C-FeN / NC-5 has an initial potential of 1.414 V, the potential can maintain good stability after 100 hours of continuous operation, with a decay rate of 6.8% ( Figure 5 c), indicating that Fe3C-FeN / NC-5 has good ORR electrocatalytic stability in practical ZAB. In order to study the rate performance of the battery, the current density was 2 to 20 mA / cm 2 The discharge test was carried out under the conditions of Figure 5 d). Compared with the commercially available Pt / C (20 wt%) based ZAB, the Fe3C-FeN / NC-5 assembled ZAB has a higher conductivity than the Fe3C-FeN / NC-5 based ZAB in terms of the return to 2.0 mA / cm 2 It shows a smaller voltage drop of only 2.2%, indicating that Fe3C-FeN / NC-5 has ideal durability and excellent recycling performance as an oxygen catalyst for ZAB cathode.

[0104] To demonstrate the feasibility of providing energy in some portable power devices, we assembled a Fe3C-FeN / NC-5 based ZAB, which exhibited a high open circuit potential of 1.531 V ( Figure 5 e). In addition, one or two batteries can be used to power an LED display with a working voltage of 1-5V and an LED light with a working voltage of 1.5V ( Figure 5 f). Therefore, the designed Fe3C-FeN / NC-5 based carbide can be used as an ORR catalyst for disposable ZAB batteries.

[0105] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF, characterized in that: The following steps are involved: S1. Dissolve H2L-N in DMF solution to form a ligand solution; mix zinc salt, iron salt and water to obtain a metal ion solution; S2, uniformly mixing the metal ion solution and the ligand solution at room temperature to obtain a reaction solution; S3, subjecting the reaction solution in S2 to a hydrothermal reaction; S4, centrifuging, washing, drying and then calcining the suspension obtained after the hydrothermal reaction in S3 to obtain the metal carbide electrocatalyst derived from Fe-doped MOF; Wherein, the structural formula of the H2L-N is as follows:

2. The method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF according to claim 1, characterized in that: In S1, the mass volume ratio of the H2L-N and DMF solution is 1 mg: 0.3-0.6 mL; the volume ratio of the total mass of the zinc salt and the iron salt to H2O is 1 mg: 0.5-0.9 mL.

3. The method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF according to claim 1, characterized in that: In S1, the mass ratio of the total mass of the zinc salt and the iron salt to the mass of H2L-N is 1-1.5:

1.

4. The method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF according to claim 1, characterized in that: In S1, the zinc salt is Zn(NO3)2·6H2O; the iron salt is Fe(NO3)3·9H2O.

5. The method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF according to claim 1, characterized in that: In S3, the temperature of the hydrothermal reaction is 70-90°C and the time is 20-35h.

6. The method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF according to claim 1, characterized in that: In S4, the centrifugal conditions are: rotation speed 8000-10000 r / min, time 3-5 min; the drying conditions are: temperature 45-55° C., time 8-12 h.

7. The method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF according to claim 1, characterized in that: In S4, the calcination includes two calcinations; the process of the two calcinations includes: loading the dried material into a porcelain boat, placing it in a tube furnace for a first heating calcination; acid leaching in a 0.3-0.6M H2SO4 solution for 20-30 hours, then loading it into a porcelain boat, and placing it in a tube furnace for a second heating calcination under the same conditions as the first heating calcination.

8. The method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF according to any one of claims 1 to 7, characterized in that: In S4, the calcination temperature is 920-950°C, the time is 1.5-2.5h, and the heating rate is 3-5°C / min.

9. A metal carbide electrocatalyst derived from Fe-doped MOF, characterized in that: The electrocatalyst is prepared by the method for preparing a metal carbide electrocatalyst derived from Fe-doped MOF as described in any one of claims 1 to 8.

10. Use of the Fe-doped MOF-derived metal carbide electrocatalyst as claimed in claim 9 as an oxygen reduction catalyst in a disposable zinc-air battery.

Citation Information

Patent Citations

  • Method for synthesizing monatomic catalyst, monatomic catalyst and application

    CN110961134A

  • Copper single atom / atom cluster catalyst and application thereof

    CN113871639A

  • Simple MOF (Metal Organic Framework) derived Fe single-site oxygen reduction electrocatalyst as well as preparation method and application thereof

    CN114243031A

  • Hybrid composite comprising metal-organic framework and two-dimensional sheet

    KR102366563B1